2014
DOI: 10.1021/jp501515g
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Differential Interacting Mechanisms of Sodium Dodecyl Sulfate with Bovine Serum Fetuin: A Biophysical Insight

Abstract: Sodium dodecyl sulfate (SDS)-glycoprotein interaction serves as a model for a biological membrane. To get mechanistic insight into the interaction of SDS and glycoprotein, the effect of SDS on bovine serum fetuin (BSF) was studied in subcritical micellar concentrations at pH 7.4 and pH 2 using multiple approaches. SDS interacts electrostatically with BSF through its negatively charged head groups at pH 2 and hydrophobically via its alkyl chains at pH 7.4 up to a 1:20 molar ratio of BSF to SDS. However, at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…We have used the average lifetime (τ avg ) of BSA instead of emphasizing the individual decay constants. The average lifetime values for the biexponential decay were calculated using equation . The lifetime components of BSA in absence and presence of ILs are shown in Table .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…We have used the average lifetime (τ avg ) of BSA instead of emphasizing the individual decay constants. The average lifetime values for the biexponential decay were calculated using equation . The lifetime components of BSA in absence and presence of ILs are shown in Table .…”
Section: Resultssupporting
confidence: 63%
“…The average lifetime values for the biexponential decay were calculated using equation 4. [68] The lifetime components of BSA in absence and presence of ILs are shown in Table 4. It is observed that the lifetime decreases in the presence of ILs with increasing concentration, which further supports the dynamic quenching of BSA fluorescence by ILs and suggests the existence of a significant interaction between ILs and BSA.…”
Section: Fluorescence Lifetime Decay Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Each spectra obtained was the average of 2 scans. The path length of the cells was 0.1 and 1 cm for far‐UV CD (190‐250 nm) and near‐UV CD (250‐300 nm) measurements . The percent of secondary structure was estimated by using online K 2 D software.…”
Section: Methodsmentioning
confidence: 99%
“…The path length of the cells was 0.1 and 1 cm for far-UV CD (190-250 nm) and near-UV CD (250-300 nm) measurements. 34,35 The percent of secondary structure was estimated by using online K 2 D software. The BSA concentration for far-and near-UV CD measurements was taken as 5μM and 10μM, respectively.…”
Section: Circular Dichroic Measurementsmentioning
confidence: 99%